The Effect of Problem Based Learning-STEM on Students' 21st Century Skills in Indonesia: A Meta-Analysis - Ilwandri Ilwandri; Abdul Rahman; Tomi Apra Santosa; Zulkifli Zulkifli; Yayat Suharyat; Suhaimi Suhaimi (Badan Penerbit STIEPARI Press, 2023)
21st century skills are skills that must be possessed by students. Students' 21st century skills are still relatively low. Problem-based learning is a learning model that encourages students to improve 21st century skills. Problem based learning-STEM in the process of student learning activities has not run optimally. This study aims to determine the effect of the Problem Based Learning-STEM model on students' 21st century skills. This research is a type of meta-analysis research. The data sources in this study came from 6 national and international journals published in 2015-2023. The process of searching for data sources through Google Scholar, ProQuest, ScienceDirect, Wiley and Eric databases. The database for each study must meet the inclusion and exclusion criteria. The heterogeneity of the data taken was analyzed with the help of the Comprehensive Meta-analysis (CMA) version 3.0 application. Meta-analysis showed an effect size value of 1.45 with very high criteria. This finding shows that the Problem Based Learning-STEM model has a significant effect on students' 21st century skills. This model needs to be applied in every school so that students have 21st century skills.